1998
DOI: 10.1021/jp972939l
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Ionophores and Salts through a Water−Chloroform Liquid−Liquid Interface:  Molecular Dynamics−Potential of Mean Force Investigations

Abstract: We report a theoretical study on the liquid−liquid interfacial behavior of the species involved in the extraction of Cs+ by a calix[4]arene-crown6 ionophore (L):  the free Cs+ Pic- and Cs+ Cl- salts, the LCs+ and LCs+ Pic- complexes, and uncomplexed L. Based on molecular dynamics simulations, we calculated the free energies changes for migration from the interface into the aqueous and the organic phases, respectively. For free L and for the LCs+ complex, with or without Pic- counterion, an energy minimum is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 63 publications
6
87
1
Order By: Relevance
“…Schweighofer and Benjamin [2,3], Lauterbach et al [4] and others noted the creation of "water fingers" trailing after transferring ions through the interface of immiscible or oil-water interfaces. Fernandes et al [5] found from their MD simulations that the Gibbs energy cost for ion transfer across the water/2-heptanone LLI increased with decreasing ion size.…”
Section: Introductionmentioning
confidence: 99%
“…Schweighofer and Benjamin [2,3], Lauterbach et al [4] and others noted the creation of "water fingers" trailing after transferring ions through the interface of immiscible or oil-water interfaces. Fernandes et al [5] found from their MD simulations that the Gibbs energy cost for ion transfer across the water/2-heptanone LLI increased with decreasing ion size.…”
Section: Introductionmentioning
confidence: 99%
“…[14] The use of molecular dynamics and Monte Carlo techniques has contributed enormously to the understanding of the surface properties and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…these methods have been widely used for a number of non-ionic [19][20][21][22][23][24][25][26][27][28] and ionic penetrants [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] at various fluid interfaces.…”
Section: Darvas Et Almentioning
confidence: 99%